2013
DOI: 10.1177/1464420712470356
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of fluid–structure interaction based blast-mitigation effects

Abstract: Advanced non-linear dynamics, finite element computational methods and tools are utilized in order to assess the blast wave mitigation potential of the fluid–structure interaction phenomena involving rigid and deformable structures. The employed computational methods and tools are verified and validated by first demonstrating that they can quite accurately reproduce analytical solutions for a couple of well-defined blast wave propagation and interaction problems. Then the methods/tools are used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Blast interactions with structures can be prohibitively complex to test experimentally, so these tests are often performed both in air and in water by scaling down the size of the experiment according to the relevant dimensionless parameters [ 17 , 22 ]. G.I.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Blast interactions with structures can be prohibitively complex to test experimentally, so these tests are often performed both in air and in water by scaling down the size of the experiment according to the relevant dimensionless parameters [ 17 , 22 ]. G.I.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor first described the pi groups that dictate the behavior of an underwater blast wave hitting a solid structure with air behind that structure, primarily in an attempt to predict damage to ships from TNT depth charges [ 23 ]. Taylor’s dimensional analysis and subsequent studies by other groups concluded that the amount of momentum transferred into a structure by a blast wave can be scaled by size if the time-relevant parameters of the blast wave are also scaled [ 22 , 23 ]. Dimensionless parameters dictating the amount of momentum transferred are shown as Eqs ( 3 ) & ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Explosives such as (TNT) and ANFO when exploded would generate blast waves that can result in extensive damages to the buildings and environments (Ngo et al, 2007). Blast waves can be defined as pressure-based waves propagating in the vicinity of the explosive charge and shock waves serve as the stress-based wave in the protective structure and in turn developed as an outcome of the interaction of structure and blast wave (Grujicic et al, 2013). The interactions of blast wave with an object ignites with an explosion followed by fast chemical reactions.…”
Section: Introductionmentioning
confidence: 99%